Rural and Urban Labour Processes: A Comparative Analysis of Australian and Canadian Development - Ferland, Jacques; Wright, Christopher (Labour/Le Travailleur, 1996)
This paper examines labour process developments within Canada and Australia during the later 19th and early 20th centuries. In contrast to traditional labour process studies, which have focused upon the development of sophisticated forms of managerial control within modern industry, this comparative analysis stresses the much simpler forms of labour control that existed within Canadian and Australian rural and urban workplaces. The paper explores the reasons underlying differences in labour process developments, and argues for the need to broaden labour process analysis in order to take account of spatial and geographic variations in working life.